2021
DOI: 10.31217/p.35.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Blue Economy goals by implementing digital technologies in the maritime transport sector

Abstract: This paper analyses how digital technologies implementation in the maritime transport sector companies can help in achieving the Blue Economy goals. Previous research offering a comprehensive overview of digital technologies in the maritime transport sector within the context of the Blue Economy is scarce. To fill this research gap, the economic effects of maritime transport are investigated, and the positive impacts of digital technologies on maritime transport are analyzed, all in the context of the Blue Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Paprocki [30] analyzes air transport and concludes that, due to the incorporation of a virtual airport hub business model based on digital technologies, the EU countries could decrease CO 2 emissions by 5% without reducing the number of passengers. Similar conclusions were obtained by Tijan et al [49] for maritime transport. The researchers highlight that digitalization boosts the generation of positive economic, social, and ecological effects.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Paprocki [30] analyzes air transport and concludes that, due to the incorporation of a virtual airport hub business model based on digital technologies, the EU countries could decrease CO 2 emissions by 5% without reducing the number of passengers. Similar conclusions were obtained by Tijan et al [49] for maritime transport. The researchers highlight that digitalization boosts the generation of positive economic, social, and ecological effects.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Authors suggested that port cities explore and implement new technologies that can contribute to better harmonization of economic, social and environmental aspects which could simultaneously increase productivity, improve safety and reduce negative environmental impacts. Tijan et al [17] researched the impact of digital technology in the context of the Blue Economy and concluded that the implementation of digital technology in the maritime transport sector has a positive impact on achieving the Blue Economy goals. As a good example, they cited the Port of Rotterdam and its development of the "Pronto" application, which is linked to models for calculation, analysis and optimization of greenhouse emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The maritime transport industry, the primary provider of the global logistics network, is regarded as one of the industries with high potential in terms of the blue growth strategy ( Fernández-Macho et al, 2015 , Tijan et al, 2021 ). However, it is a highly vulnerable and risky sector with respect to unexpected events such as global economic developments, freight price volatility, financial crises, political events, and diseases ( Stopford, 2009 , Lun et al, 2010 , Tatenhove, 2021 , Yin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the outbreak of Covid-19, the worldwide maritime transportation industry that accounts for 90% of the international trade and supply of cargo presents new and unprecedented impacts on the maritime transportation-related industry ( Narasimha et al, 2021 , Charłampowicz, 2021 , Tatenhove, 2021 , Tijan et al, 2021 , Koyuncu et al, 2021 ). Specifically, the public health measures adopted to prevent the spread of the Covid-19 pandemic resulted in a sharp decline in consumer expenditure and a suspension of face-to-face services, including travel, entertainment, and catering ( Notteboom et al, 2021 , Remes et al, 2021 , Hossain, 2021 , Chen et al, 2022 , Pan and He, 2022 , Downey et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%